Cover Image, Volume 11, Issue 6. (7th November 2017) - Woolf, Dominic; Lehmann, Johannes; Joseph, Stephen; Campbell, Christopher; Christo, Farid C.; Angenent, Largus T.
Abstract : The cover image, by Dominic Woolf et al., is based on the In the Field An open‐source biomass pyrolysis reactor, DOI:10.1002/bbb.1814 . Abstract : The cover image, by Dominic Woolf et al., is based on the In the Field An open‐source biomass pyrolysis reactor, DOI:10.1002/bbb.1814 .